2021
DOI: 10.3389/fgene.2021.671552
|View full text |Cite
|
Sign up to set email alerts
|

The Co-occurrence of Chronic Hepatitis B and Fibrosis Is Associated With a Decrease in Hepatic Global DNA Methylation Levels in Patients With Non-alcoholic Fatty Liver Disease

Abstract: Global DNA hypomethylation has been reported in patients with chronic hepatitis B (CHB) and non-alcoholic fatty-liver disease (NAFLD). However, the global DNA methylation profile of patients with concurrent NAFLD and CHB (NAFLD + CHB) is still unclear. We aimed to detect the hepatic global DNA methylation levels of NAFLD + CHB patients and assess the associated risk factors. Liver biopsies were collected from 55 NAFLD patients with or without CHB. The histological characteristics of the biopsy were then assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Hepatitis B virus (HBV) is one of the most serious threats to human life, health, and safety. According to the statistics of relevant institutions, there are about 2 billion patients who have been infected with HBV worldwide, of which about 400 million infected patients develop Chronic Hepatitis B (CHB) [ 1 ]. While China, as one of the globally recognized populous countries, has up to 20 million CHB patients, accounting for approximately 5% of CHB patients worldwide [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hepatitis B virus (HBV) is one of the most serious threats to human life, health, and safety. According to the statistics of relevant institutions, there are about 2 billion patients who have been infected with HBV worldwide, of which about 400 million infected patients develop Chronic Hepatitis B (CHB) [ 1 ]. While China, as one of the globally recognized populous countries, has up to 20 million CHB patients, accounting for approximately 5% of CHB patients worldwide [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study found that patients with concurrent NAFLD and CHB exhibited lower levels of global DNA methylation than patients with NAFLD alone. The concurrence of CHB and liver fibrosis in NAFLD patients was associated with a decrease in the global DNA methylation levels [87] . NAFLD-related cumulative fat deposition, oxidative stress, and inflammatory responses may produce a pro-fibrotic and pro-cancer environment in the liver and further accelerate the development of cirrhosis and HCC.…”
Section: Progression and Outcomes Of Chb With Nafldmentioning
confidence: 99%
“…The concurrence of CHB and liver fibrosis in NAFLD patients was associated with a decrease in the global DNA methylation levels. [ 87 ] NAFLD-related cumulative fat deposition, oxidative stress, and inflammatory responses may produce a pro-fibrotic and pro-cancer environment in the liver and further accelerate the development of cirrhosis and HCC. However, the disease progression is influenced by various confounding factors, and the interaction between HBV and metabolic homeostasis in the progression of liver disease requires further study.…”
Section: Progression and Outcomes Of Chb With Nafldmentioning
confidence: 99%